Pearls & Oy-sters: Cerebral Venous Congestion Associated With Cognitive Decline Treated by Jugular Release. (27th September 2022) - Primiani, Christopher T.; Lawton, Michael; Hillis, Argye Elizabeth; Hui, Ferdinand K.
Abstract : Cognitive dysfunction is often multifaceted and can be seen across all age groups in medicine. The combination of cognitive decline and increased intracranial pressure may suggest possible anatomical abnormalities. We present a case report from our academic center that describes a young man with new cognitive fatigue and brain fog in the setting of increased venous pressure that resolved with surgical intervention at a site of jugular vein stenosis. We discuss current hypotheses from basic and clinical research related to pathophysiology underlying venous vascular congestion and associated neurologic disorders. Further research is warranted to elucidate the underlying mechanisms of venous congestion and cognition to better identify therapies and improve quality of life for patients.